'Véote, y no te conozco': the unrecognizable form of Cervantes's El rufián dichoso - Thacker, J (Maney Publishing, 2009)
This study takes a close look at one of Miguel de Cervantes's Ocho comedias, (1615), El rufián dichoso, examining the apparently chaotic dramatic form of the play. It suggests that, as has been documented for other works in his collection of unperformed pieces, Cervantes wanted, in this religious play, to comment upon and parody the form of the new drama as it had developed under Lope de Vega and his followers. Analysis of the play would suggest that Cervantes was not only interested in what he perceived to be the failings in others' dramatic work, but in constructing a play whose form would reflect on its content, producing a rich theatrical experience for the audience. An appreciation of Cervantes's drama (similar to the appreciation shown for his prose works) reveals him to be a more significant figure in the history of Spanish theatre than has usually been acknowledged.